Mobile banking adoption its antecedents and post-adoption effects: the role of consumers status orientation in an African context - Alphonse Mefoute Badiang; Emile Saker Nkwei (Cogent Business & Management, 2024)
This study examines the antecedents of Mobile banking (M-banking) app adoption, explores post-adoption effects, and tests the moderating effect of consumer status orientation on the relationship between adoption intention and its consequences. The conceptual model hypothesized 20 relationships, including 10 moderations. Hypotheses are tested using the structural equation modeling method (PLS-SEM) on a sample of 509 individuals. The results reveal that the main variables of `users' rational perception, namely behavioral control and terminal security, significantly influence the intention to adopt the application, which in turn impact relationship quality and financial inclusion. However, hedonic expectations do not have a significant impact on the intention to adopt the application; the impact of culture in these relationships is further established; indeed, traditional and modern values moderate the impact of the intention to adopt the application on key post-adoption factors, financial inclusion, and relationship quality. The main recommendations and limitations of the research are discussed.
Keywords: 650; M-banking; status orientation; financial inclusion; relationship quality; structural equation modeling